(untitled) (Applied Biological Research, 2012)
Poultry industry is one of the promising industries of West Bengal (India) exhibiting annual growth rate of 15.4% since last 5 years. West Bengal state stands 2nd in relation to poultry population and 1st with respect to human population density in India (FAO, 2008). However, the State stands 5th in egg production due to large number of low yielding fowl population, about 84% of which are produced in backyard farming system (Animal Resources Development Department, 2010). ‘Deshi’ hens contribute 50% to egg production and the rest is from duck. The average productivity of backyard fowl population in the State is about 99 eggs in a year (Animal Resources Development Department, 2010). Microbial infection present within the flock in any form is one of the major constraints in optimum egg production. Escherichia coli is one of the common microbial flora of gastrointestinal tract of poultry and human being but may be pathogenic to both (Jawetz et al., 1984). Besides E. coli, colibacillosis in poultry is of great zoonotic importance as poultry meat is the common source of animal protein in India. In addition, the bacterial isolates of poultry or its products are the major source of antimicrobial resistance gene that can be horizontally transferred into other bacteria present in the environment (Guerra et al., 2003). The infection of animals or human with such kind of resistant bacteria makes the treatment difficult. In this background the present investigation was envisaged to know the prevalence of E. coli along with their antibiotic resistance pattern in the backyard chickens of West Bengal.